The importance of virtual museums in the formation of students 'educational competencies on fine literacy - Sadatov, Chori (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The article is scientifically and practically based on the importance of virtual museums in shaping the interest of school students inthe fine arts and in shaping the educational competencies of students in the field of fine literacy